Padrões hemodinâmicos hepáticos na esteatose não alcóolica: avaliação pela ultrassonografia com doppler e estudo histológico - Monteiro, Maria Luiza Gonçalves dos Reis (2015)
Nonalcoholic fatty liver disease (NAFLD) is a prevalent condition and frequently diagnosed in ultrasonography (US). Bidimensional ultrasonography steatosis grading is subjective and subject to interobserver and intraobserver variability. Hepatic biopsy is the standard diagnostic method, but its indication has some controversies. For clinical practice, noninvasive, objective and reproducible steatosis quantification is necessary. The aim of this study is to assess the performance of Doppler US indices of the three major hepatic vessels in steatosis diagnosis and grading, having histological study as reference. Doppler US was performed in 98 volunteers, including 49, with NAFLD who were submitted to liver biopsy. The other 49, without steatosis in US and without risk factors for NAFLD, were included as the healthy group and were not submitted to biopsy due to ethical reasons. Portal venous pulsatility index (PVI) was calculated by subtracting the minimal peak of portal velocity from the maximum peak and dividing the result by the maximum peak. Right hepatic vein waveform pattern (HVWP) was classified as monophasic, biphasic or triphasic. Hepatic artery resistance index (HARI) was calculated by subtracting end diastolic velocity from systolic peak velocity and dividing the result by systolic peak velocity. Hepatic artery pulsatility index (HAPI) was calculated subtracting end diastolic velocity from systolic peak velocity and dividing the result by mean velocity. Hepatic biopsy specimens were classified in mild steatosis (less than 33% of fatty hepatocytes), moderate (33 to 66%) and severe (more than 66%). Inflammation and fibrosis were classified according to intensity and localization in hepatic acini. PVI had inverse and significant correlation with steatosis presence in biopsy (r= - 0.69; p <0.0001). PVI media and standard deviation in healthy group was 0.35 ±0.08 and in steatosis group was 0.21±0.10 (p<0.0001). HVWP was predominantly triphasic in healthy group and in mild steatosis subgroup while monophasic pattern was the most frequent in moderate and severe steatosis. HARI and HAPI did not distinguish healthy from steatosis group. None of the indices significantly correlated with steatosis grading. Hemodynamic changes in portal and hepatic veins allow noninvasive steatosis diagnoses. In order to improve diagnostic capacity, a discriminant function was obtained using these two parameters, resulting in improvement of Doppler specificity, sensibility and accuracy for steatosis diagnostic. This is a simple and clinical applicable analysis. Doppler indices have limitations in quantifying steatosis as in diagnosing inflammation and fibrosis.